2013
DOI: 10.1007/s11745-013-3827-x
|View full text |Cite
|
Sign up to set email alerts
|

EPA and DHA Levels in Whole Blood Decrease More Rapidly when Stored at −20 °C as Compared with Room Temperature, 4 and −75 °C

Abstract: High-throughput n-3 fatty acid profiling is enabled by collection techniques such as venous whole blood and fingertip prick (FTP) sampling, but the resulting increased sample numbers increases storage demand. Highly unsaturated fatty acids (HUFA) in erythrocytes are susceptible to oxidation, but this tendency is poorly characterized in venous and FTP whole blood. Presently, whole blood samples with low and high n-3 content collected with ethylenediaminetetraacetic acid were stored on chromatography paper with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 38 publications
1
55
0
2
Order By: Relevance
“…nach der Bestimmung eines Blutbildes aus venösem Blut noch vorhanden ist. Die Fettsäurezusammensetzung von Erythrozyten ist bei Umgebungstemperatur mindestens eine Woche stabil, weshalb der Versand der Proben unproblematisch ist [7,8]. Bei -80°C ist die Fettsäurezusammensetzung der Erythrozyten über viele Jahre stabil, während sie sich bei -20°C schon nach wenigen Tagen verändert (7,8).…”
Section: Methodikunclassified
“…nach der Bestimmung eines Blutbildes aus venösem Blut noch vorhanden ist. Die Fettsäurezusammensetzung von Erythrozyten ist bei Umgebungstemperatur mindestens eine Woche stabil, weshalb der Versand der Proben unproblematisch ist [7,8]. Bei -80°C ist die Fettsäurezusammensetzung der Erythrozyten über viele Jahre stabil, während sie sich bei -20°C schon nach wenigen Tagen verändert (7,8).…”
Section: Methodikunclassified
“…Data are presented as nmol fatty acid per 100 μL blood, mean ± SD, n = 4 SFA saturated fatty acid, MUFA monounsaturated fatty acid, PUFA polyunsaturated fatty acid and HUFA highly unsaturated fatty acid of analysis. We have previously shown that storage of the whole blood samples under these conditions will not significantly affect the fatty acid profile for up to 6 months [13], and all analyses were performed within 3 months of storage. For analysis, whole blood samples were removed from storage and allowed to thaw on ice.…”
Section: Microwave-assisted Direct Transesterification Of Whole Bloodmentioning
confidence: 99%
“…Aliquots (25 μL) of the whole blood were applied to pre-washed chromatography strips as described previously [13] and allowed to dry in air for approximately 30 min. DBS were then transesterified by the 5-min, 30-W microwave method or 3 h standard 1 % H 2 SO 4 method as previously described, or for 1 h at 95 °C with 1 mL 14 % boron trifluoride in methanol with 0.3 mL hexane.…”
Section: Microwave-assisted Transesterification Of Dried Blood Spots mentioning
confidence: 99%
See 1 more Smart Citation
“…The GC settings were as previously described [221]. Peaks were identified by retention times through comparison to an external mixed standard sample (GLC-462, Nu…”
Section: Lipid Extraction and Quantificationmentioning
confidence: 99%